Structure of Leishmania donovani 6-Phosphogluconate Dehydrogenase and Inhibition by Phosphine Gold(I) Complexes: A Potential Approach to Leishmaniasis Treatment - Berneburg, Isabell; Stumpf, Michaela; Velten, Ann-Sophie; Rahlfs, Stefan; Przyborski, Jude; Becker, Katja; Fritz-Wolf, Karin; Justus Liebig University Giessen (My University, 2023)
As unicellular parasites are highly dependent on NADPH as a source for reducing equivalents, the main NADPH-producing enzymes glucose 6-phosphate dehydrogenase (G6PD) and 6-phosphogluconate dehydrogenase (6PGD) of the pentose phosphate pathway are considered promising antitrypanosomatid drug targets. Here we present the biochemical characterization and crystal structure of Leishmania donovani 6PGD (Ld6PGD) in complex with NADP(H). Most interestingly, a previously unknown conformation of NADPH is visible in this structure. In addition, we identified auranofin and other gold(I)-containing compounds as efficient Ld6PGD inhibitors, although it has so far been assumed that trypanothione reductase is the sole target of auranofin in Kinetoplastida. Interestingly, 6PGD from Plasmodium falciparum is also inhibited at lower micromolar concentrations, whereas human 6PGD is not. Mode-of-inhibition studies indicate that auranofin competes with 6PG for its binding site followed by a rapid irreversible inhibition. By analogy with other enzymes, this suggests that the gold moiety is responsible for the observed inhibition. Taken together, we identified gold(I)-containing compounds as an interesting class of inhibitors against 6PGDs from Leishmania and possibly from other protozoan parasites. Together with the three-dimensional crystal structure, this provides a valid basis for further drug discovery approaches.
Keywords: leishmaniasis; 6-phosphogluconate dehydrogenase; pentose phosphate pathway; auranofin; phosphine gold(I)-complexes; ddc:570